New insights of necroptosis and immune infiltration in sepsis-induced myocardial dysfunction from bioinformatics analysis through RNA-seq in mice - Du, Yan; Zhong, Ying; Ding, Ruilin; Wang, Xiaojie; Xia, Fenfen; Zhang, Qian; Peng, Qing (Frontiers in Cellular and Infection Microbiology, 2022)
Sepsis is a life-threatening organ dysfunction caused by dysregulated host immune response to infection. Sepsis-induced myocardial dysfunction (SIMD) is a common complication in patients with severe sepsis and is associated with increased mortality. The molecular mechanisms underlying SIMD are complex and not well characterized. Excessive inflammation due to impaired regulation of immune response is one of the major causes of SIMD. Necroptosis is a novel type of cell death that is closely related to tissue injury and inflammation. However, the role of necroptosis in SIMD is not known. Therefore, in this study, we performed an in-depth bioinformatics analysis to investigate the relationship between necroptosis and SIMD using a mouse model generated by intraperitoneal injection of lipopolysaccharide (LPS) and the underlying mechanisms. Myocardial function was assessed by echocardiography. Histopathological changes in SIMD were analyzed by hematoxylin and eosin (H&E) staining. Gene expression profiles of the heart tissues from the SIMD and control mice were analyzed by bioinformatics analysis. Transcriptome sequencing demonstrated significant differences in the expression levels of 3654 genes in the heart tissues of SIMD mice including 1810 up-regulated and 1844 down-regulated genes. The necroptosis pathway genes were significantly enriched in the heart tissues from the SIMD group mice. We identified 35 necroptosis-related differentially expressed genes (NRDEGs) including MLKL and RIPK3. Cardiomyocyte necroptosis was confirmed by qRT-PCR and western blot analysis. The expression levels of most NRDEGs showed positive correlation with the infiltration levels of mast cells, macrophages, and neutrophils, and negative correlation with the infiltration levels of B cells and plasma cells in the heart tissues of the SIMD group mice. In conclusion, this study demonstrated that necroptosis was associated with changes in the infiltration levels of several immune cell types in the heart tissues of the SIMD model mice. This suggested that necroptosis influenced SIMD development by modulating the immune microenvironment. This suggested that NRDEGs are potential diagnostic biomarkers and therapeutic targets for patients with SIMD.